Thawing plateau time indicating the duration of phase transition from ice to water is the strongest predictor for long-term durable pulmonary vein isolation after cryoballoon ablation for atrial fibrillation—Data from the index and repeat procedures - Shi, Li-Bin; Wollner, Kristian; Chu, Song-Yun; Wang, Yu-Chuan; Solheim, Eivind; Schuster, Peter; Chen, Jian (Frontiers in Cardiovascular Medicine, 2023)
Introduction This study aimed to clarify the relationship between the durability of pulmonary vein (PV) isolation and the time of phase transition from ice to water indicated by thawing plateau time in a cryoballoon ablation for atrial fibrillation (AF). Methods and results In this retrospective study, 241 PVs from 71 patients who underwent a repeat AF ablation 526 (IQR: 412, 675) days after a cryoballoon ablation were analyzed. Reconnection was observed in 101 (41.9%) PVs of 53 patients (74.6%). Thawing plateau time (TimeTP) was defined as the time from 0°C to 10°C inside the balloon in the thawing period. Durable PV isolation was associated with significantly longer TimeTP compared with PV reconnection (26.0 vs. 11.0 s, P < 0.001). The proportion of durable PV isolations increased with TimeTP in a dose-proportional manner. The cut point for PV reconnection was TimeTP <15 s with a positive predictive value of 82.1% (sensitivity = 63.4%, specificity = 90.0%) while for durable PV isolation the cut point was TimeTP >25 s with a positive predictive value of 84.6% (sensitivity = 55.0%, specificity = 86.1%). In the analysis of multivariable logistic regression, location of PV reconnection (P < 0.01), TimeTP (P < 0.05) and thawing plateau integral (P < 0.01) were shown as independent predictors for durable PV isolation. Conclusion TimeTP is an independent predictor for the durability of PV isolation, and it presents in a dose-proportional manner. TimeTP <15 s predicts long-term reconnection while TimeTP >25 s predicts durable PV isolation.